Inhibitory effect of calcium on non-heme iron absorption may be related to translocation of DMT-1 at the apical membrane of enterocytes. - Thompson, B; Sharp, P; Elliott, R; Fairweather-Tait, S (2010)
Many studies show that calcium reduces iron absorption from single meals, but the underlying mechanism is not known. We tested the hypothesis that calcium alters the expression and/or functionality of iron transport proteins. Differentiated Caco-2 cells were treated with ferric ammonium citrate and calcium chloride, and ferritin, DMT-1, and ferroportin were quantified in whole-cell lysate and cell-membrane fractions. Calcium attenuated the iron-induced increase in cell ferritin levels in a dose-dependent manner; a significant decrease was seen at calcium concentrations of 1.25 and 2.5 mM but was only evident after a 16-24 h incubation period. Calcium and iron treatments decreased DMT-1 protein in Caco-2 cell membranes, although total DMT-1 in whole cell lysates was unchanged by either iron or calcium. No change was seen in ferroportin expression. Our data suggest that calcium reduces iron bioavailability by decreasing DMT-1 expression at the apical cell membrane, thereby downregulating iron transport into the cell.